PENGEMBANGAN MEDIA PEMBELAJARAN MICROSOFT WORD MELALUI SEMINAR UNTUK SISWI SMK IBRAHIMY 1 SUKOREJO DALAM MENINGKATKAN KREATIVITAS DAN KETERAMPILAN DIGITAL - Ummul Khoirun Fitriyah; Wulan Shelfiana Kamil; Zaehol Fatah (CV. Denasya Smart Publisher, 2025)
This community service activity aims to improve the digital skills and creativity of students at SMK Ibrahimy 1 Sukorejo through the development of learning media based on Microsoft Word. Mastery of word processing software is a crucial skill for vocational school students, especially in facing the increasingly digital work environment. The activity was carried out in the form of an educational seminar consisting of three sessions: theoretical presentation, demonstration of Microsoft Word features, and independent practice. Evaluation was conducted through observation, analysis of students' practice documents, and a satisfaction questionnaire. The results showed that more than 85% of participants experienced an improvement in technical skills related to official letters, reports, and promotional pamphlets. In addition, 86.6% of participants expressed satisfaction with the training method. This activity has proven effective in enhancing digital literacy and creativity through a hands-on learning approach. Therefore, this seminar can serve as a model for implementing digital skills training in vocational education settings.